Serotonergic and Cholinergic Strategies as Potential Targets for the Treatment of Schizophrenia - Nikiforuk, Agnieszka (Current Pharmaceutical Design, 2016)
Currently availably antipsychotic drugs are effective in ameliorating the positive symptoms of schizophrenia. Nevertheless, the cognitive impairments and negative symptoms experienced by schizophrenia patients still await effective treatment. In particular, potential cognitive enhancers have received considerable attention in the field of schizophrenia research. From among the multiple therapeutic approaches that have recently been proposed, this review will focus on serotonin receptors, namely 5-HT5ARs, 5-HT6Rs and 5-HT7Rs, and on alpha 7 nicotinic acetylcholine receptors (α7-nAChRs). The purpose of this review is to summarise existing data regarding the effects of ligands of these receptors on measures of schizophrenia-like behaviours in animal models, with particular emphasis on their procognitive effects. Existing clinical data will also be reported, and the potential clinical efficacy of these compounds will be discussed with regard to the preclinical results. Possible explanations for the lack of clinically validated evidence and for the discrepancies between the clinical and preclinical data will also be provided.
Keywords: animal models